The Romance of the Three Kingdoms on Panel Painting From the Old Sermon Hall at Wat Nak Prok - Klinhom, Tapakorn (Journal of Arts and Thai Studies, 2025)
Background and Objectives: The Romance of the Three Kingdoms on the panel painting in the old sermon hall at Wat Nak Prok is a Chinese art in a Thai temple, in Bangkok, that has been forgotten by both the public and private sectors. This painting is known in small circles and lacks study and analysis in the context of form, meaning, and determining age. This research aimed to study and analyze the content found on the panel painting to determine the age of the panel painting in the old sermon hall at Wat Nak Prok. Methods: This was qualitative research with an emphasis on analytical study and art historical research methodology. Data were collected from both primary and secondary sources. Primary evidence was gathered through field surveys, including photographing and examining the mural paintings and architectural features of the sermon hall. Secondary evidence included relevant documents. The collected data were analyzed by interpreting the paintings and comparing them with artworks in other temples according to the principles of iconography. Additionally, the murals were compared with The Romance of the Three Kingdoms to address the research objectives. The results were then summarized and presented. Results: The results revealed that The Romance of the Three Kingdoms were tempera paintings on wooden panels, created by Chinese artists during the reign of His Majesty King Nang Klao (King Rama III), dating no earlier than 1847. There are 11 episodes of the paintings of The Romance of the Three Kingdoms, namely: the plan to burn Xīnyě; Zhāng Fēi breaks through enemies; a fight between Zhūgě Liàng and Mùlù Dàwáng; the battle of Hulao Pass; the battle of Red Cliffs panel discussion; Liú Bèi took Sūn Fūrén and fled back to Jingzhou; The battle of Bómǎ; Cáo Cāo was granted an audience with Emperor Xian of Han; the mansion of Liú Bèi and Sūn Fūrén; The oath-taking ceremony performed by Cáo Cāo and the seventeen city lords; and the battle of Chángbǎn. Application of this study: The results can help integrate the knowledge of Thai Buddhist decorations with Chinese art in the style of the royal style of His Majesty King Nang Klao (King Rama III). This also helps prevent the panel paintings on the sermon hall from disappearing and provides data for scholars and those interested in studying Chinese Studies in Thailand. Conclusions: The Romance of the Three Kingdoms as decoration in Thai Buddhist sites in Bangkok was very popular during the reign of His Majesty King Nang Klao (King Rama III), found in six sites. The Romance of the Three Kingdoms as decoration in Thai Buddhist sites also reflects the understanding of the content of the literature of Thai people in the past, reflecting the popularity of The Romance of the Three Kingdoms through artworks in Thai society well.